MODAL SOSIAL DAN KETERPILIHAN UMI AZIZAH PADA PILKADA KABUPATEN TEGAL TAHUN 2018 - Dita Amalia Safitri; Muhammad Adnan (Journal of Politic and Government Studies, 2020)
This study analyzes how the strength and utilization of Umi Azizah's social capital as oneof the factors influencing his victory in the 2018 Tegal Regency elections. The method used isa qualitative method with a descriptive approach. Data is collected through interview anddocumentation. The results of this study indicate that social capital as a social network ownedby Umi Azizah in participating in the 2018 Tegal Regency elections is her position as a santriwith a Bachelor of Government Science, Chair of PC Muslimat NU as well as preachers, andincumbent. The social network is used optimally as a political network through consolidationbetween networks and intense interaction with the community.Keywords: Local Election, Social Capital, Network Utilization.